Geo. T. McLauthlin & Co. - Drop-Tube Safety Steam Boilers - Sampson, Murdock, & Co. (Tufts Archival Research Center, 2005)
Page image of Geo. T. McLauthlin & Co. - Drop-Tube Safety Steam Boilers from the 1885 Boston city directory.